2022
DOI: 10.1039/d2sc02786k
|View full text |Cite
|
Sign up to set email alerts
|

An atomically precise silver nanocluster for artificial light-harvesting system through supramolecular functionalization

Abstract: Designing an artificial light-harvesting system (LHS) with high energy transfer efficiency has been a challenging task. Herein, we report an atom-precise silver nanocluster (Ag NC) as a unique platform to...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(49 citation statements)
references
References 63 publications
2
47
0
Order By: Relevance
“…In general anion template mono-layered Ag( i ) core-based NCs are not emissive in both solution and solid-states at room-temperature (298 K). 20–24 Here also we could not identify the steady-state PL properties of NC 1 and NC 2 in the DCM medium. However, after irradiation at 353 nm, strong photoluminescence is detected for NC 3 with an emission maximum at 402 nm (Fig.…”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations
“…In general anion template mono-layered Ag( i ) core-based NCs are not emissive in both solution and solid-states at room-temperature (298 K). 20–24 Here also we could not identify the steady-state PL properties of NC 1 and NC 2 in the DCM medium. However, after irradiation at 353 nm, strong photoluminescence is detected for NC 3 with an emission maximum at 402 nm (Fig.…”
Section: Resultsmentioning
confidence: 83%
“…Although the Ag NCs have attracted us with their outstanding luminescence property, most of the Ag(I) NCs are unable to exhibit their luminescence properties at room temperature due to their thermally activated dominant non-radiative transition. [20][21][22][23][24] So, the complex synthesis process of making Ag(I) NCs would not be beneficial due to the absence of their most alluring property. Very recently, Li et al showed the effect of post-synthetic modification through ligand exchange on a structurally defined Ag 20 NC in photoluminescence (PL) generation by achieving more rigidity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…56 Recently, Ag 16 S 8 clusters with similar geometrical structures have been reported by several groups. 56,60,61 Among these structures, the R/S-Ag 17 clusters exhibited the phenomenon of supramolecular chirality (Table S3). In order to understand the origin of enantiomeric self-assemblies of R-Ag 3a and 3b).…”
Section: Synthesis and Characterization Of R/s-ag 17 Clustersmentioning
confidence: 81%
“…One of the well-known strategies is to use macrocyclic ligands that form porous organic cages, which show a good perspective in adjusting the inner pore size and encapsulating well-dispersed metal aggregates. , In this context, the macrocycle with donor atoms such as O, N, or S atoms reveals great affinity to the attached guest cluster and great stability due to the high steric hindrance of the aromatic rings. , However, the size and the geometry of the encapsulated clusters or NPs are constrained by the host molecules in this macrocyclic template-directed strategy. In the past few decades, the anion-template strategy has been explored and applied to synthesize high-nuclearity silver clusters because the Ag­(I) ions exhibit a soft acceptor characteristic and flexible coordination to display structural diversity, arousing the interest of synthetic scientists. The rationale for this strategy is to use the anion as the central template core leading to the aggregation of Ag­(I) ions, which are further stabilized by the ligands such as monothiolate, ,,,, , dithiolate, ,,, diphosphine, , phosphonate, carboxylate, ,,,,,,,, alkynyl ligands, ,,,,,, metalloligand, , and their combinations. Since there are no external constraints, the cluster nuclearity can be greatly increased.…”
Section: Introductionmentioning
confidence: 99%